Gas chromatography coupled with ion trap mass spectrometry (GC-MS and GC-MS-MS) - for arson debris analysis - Rohwer, Egmont Richard (University of Pretoria, 2013)
Dissertation (MSc (Applied Chemistry))--University of Pretoria, 2007.